PERSONIFICATION IN POEM KATA YANG TAK SEMPAT TERUCAP BY RADINDA ANGGIA - Ellen Gladys Yunita Manueke (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2021)
The title of this research is Personification in the lyrics of the poem Kata Yang Tak Sempat Terucap by Radinda Anggia. The purpose of this study is to find the types of personification and the function of the meaning contained in the poem. The research method used in this study is a qualitative method in which the writer collects data from the lyrics of the poem, classifies it in personification figure of speech and then collects data and explains the types of personification and their meaning. Based on the theory used in this study, there are two types of personification found in the data, namely: verb personification and noun personification. There are 63 sentences using personification which are classified into 61 sentences expressing the personification of the verb and two sentences referring to the personification of the noun